Market Structure, Scale Efficiency, and Risk as Determinants of German Banking Profitability - Peiyi Yu; Werner Neus (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2005)
The Scale-Efficiency version of the Efficient-Structure Hypothesis and the Structure-Conduct-Performance Hypothesis find empirical support in German banking data from 1998 to 2002. Due to the acceptance of the two hypotheses and the existence of overall economies of scale, we conclude that German banks may improve their profitability by increasing their asset size and/or by consolidation. The increased banking profitability will not only come from monopolistic power (higher concentration rate) but also from the scale efficiency benefit. We also find that portfolio risk is a key factor in determining the profit-structure relationship.
urn:nbn:de:bsz:21-opus-17875
Keywords: L11; G14; G21; C33; 330; Profit-structure relationship; Market Structure; Scale efficiency; Portfolio Risk; Bank; Rentabilität; Struktur-Performance-Modell; Skalenertrag; Bankrisiko; Schätzung; Deutschland